Public mental health: a psychiatry and public health perspective. (29th March 2023) - Lyne, J.; Connellan, L.; Ceannt, R.; O'Connor, K.; Shelley, E.
Abstract: Mental health issues are fast becoming one of society's greatest health challenges with evidence of higher levels of illness and strain on psychiatric services. The reasons for this trend of increasing mental health problems across the population are complex and there is an urgent need to research and deliver effective public mental health strategies. In this perspective piece we argue that psychiatrists and public health physicians have unique knowledge and perspectives on population mental health. The development of interdisciplinary initiatives and training posts would result in clinicians with expertise to drive forward public mental health strategies. Focused and sustained advocacy and collaboration are necessary for prioritisation of public mental health on policymakers' agendas.